2021
DOI: 10.1097/wnr.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Maternal corticosteroids and depression during gestation and decreased fetal heart rate variability

Abstract: Objective Maternal depression during gestation is an adverse factor in fetal brain development that manifests in later childhood behavioral problems. Fetal heart rate variability (FHRV) mediated by parasympathetic input is a marker of gestational nervous system development. Biological mediators of adverse effects of maternal depression may involve the mother's corticosteroids; however, links between depression, corticosteroids, and early nervous system development remain inconclusive.Methods Heart rate was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Specifically, offspring of women in the symptomatic group with greater exposure to maternal CM had lower FHRV, especially males. This result is consistent with previous studies, including in our own work, providing evidence for an association between increased maternal prenatal distress and lower FHRV 15,22 . As previously discussed, lower FHRV is associated with a more reactive temperament in infancy, and can indicate less adept emotion regulation as well as biological sensitivity and susceptibility to stress and stress‐related psychopathology 52 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, offspring of women in the symptomatic group with greater exposure to maternal CM had lower FHRV, especially males. This result is consistent with previous studies, including in our own work, providing evidence for an association between increased maternal prenatal distress and lower FHRV 15,22 . As previously discussed, lower FHRV is associated with a more reactive temperament in infancy, and can indicate less adept emotion regulation as well as biological sensitivity and susceptibility to stress and stress‐related psychopathology 52 …”
Section: Discussionsupporting
confidence: 92%
“…FHRV typically increases throughout gestation, and lower FHRV has been associated with a more reactive temperament (i.e., greater irritability), 17 which, in turn, is a risk factor for childhood and adolescent neuropsychiatric disorders including depression, anxiety, attention‐deficit hyperactivity disorder, and behavioral problems 18–21 . We and others have shown that increased maternal prenatal distress is associated with lower FHRV 15,22 . However, some have found evidence to suggest accelerated development where maternal distress was associated with increased FHRV, and others found no association 16 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Many studies show that gestational psychological and emotional complications influence maternal, fetal, newborn, and even infant wellbeing. The scientific literature reports adverse outcomes such as premature delivery, longer and instrumental deliveries, low birth weight, and even alterations in the physical and cognitive development of the baby, as well as in the mother–child relationship [ 32 , 33 , 34 ].…”
Section: Mental and Emotional Status During Pregnancymentioning
confidence: 99%